1982
DOI: 10.1007/bf00400387
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenicity and invasiveness of Salmonella species

Abstract: A large number of enterotoxigenic strain was encountered in a group 56 Salmonella cultures belonging to 8 species viz., S. alachua, S. anatum, S. dublin, S. Enteritidis, S. hindmarsh, S. newport, S. typhimurium, S. weltevreden, and 5 serotypes of S. arizona (16:z4:--; 48:1,v:z56; 53:z52:z53; 60:r:z; 60:i:z53). These cultures were isolated mainly from humans and animals suffering from gasteroenteritis. The enterotoxigenic (diarrhoeagenic) Salmonella cultures possess capacities for both skin permeation and epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The comparison with models for salmonellosis is further complicated by the observation that the mouse strain used can influence results obtained in the infant suckling mouse assay (42a). This may be the reason why studies using infant Swiss mice did not observe enteropathogenicity of S. typhimurium strains (20,34). Therefore, the use of BALB/c mice may be recommended for future studies using this animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison with models for salmonellosis is further complicated by the observation that the mouse strain used can influence results obtained in the infant suckling mouse assay (42a). This may be the reason why studies using infant Swiss mice did not observe enteropathogenicity of S. typhimurium strains (20,34). Therefore, the use of BALB/c mice may be recommended for future studies using this animal model.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that enterotoxigenic properties are vital for pathogenesis of Salmonella diarrhea. Vascular permeability reaction in rabbit skin has been shown to demonstrate enterotoxigenic potential of Salmonella by several workers (Kaura et al 1982;Chary et al, 1993). Culture filtrates of Salmonella have been shown to produce two skin permeability factors (PF).…”
Section: (9459%)mentioning
confidence: 99%